2021
DOI: 10.1103/physrevlett.126.147202
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-Striction Driven Ultrafast Nonthermal Lattice Dynamics in NiO

Abstract: We use femtosecond electron diffraction to study ultrafast lattice dynamics in the highly correlated antiferromagnetic (AF) semiconductor NiO. Using the scattering vector (Q) dependence of Bragg diffraction, we introduce a Q-resolved effective lattice temperature, and identify a nonthermal lattice state with preferential displacement of O compared to Ni ions, which occurs within ~0.3 ps and persists for 25 ps. We associate this with transient changes to the AF exchange striction-induced lattice distortion, sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…The reduction of the MOBF signal is attributed to a reduction of the antiferromagnetic order in NiO. This conclusion is based on a recent time-resolved diffraction study which revealed a clear correlation between the reduction of the rhombohedral distortion of NiO and the change in the AFM order of the system [39]. Moreover, the transient MOBF traces reveal a coherent oscillation with a frequency of 130 GHz that is superimposed onto the incoherent MOBF signal [8][9][10].…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The reduction of the MOBF signal is attributed to a reduction of the antiferromagnetic order in NiO. This conclusion is based on a recent time-resolved diffraction study which revealed a clear correlation between the reduction of the rhombohedral distortion of NiO and the change in the AFM order of the system [39]. Moreover, the transient MOBF traces reveal a coherent oscillation with a frequency of 130 GHz that is superimposed onto the incoherent MOBF signal [8][9][10].…”
mentioning
confidence: 73%
“…To compare our simulations with the experimental findings, we translate the spin temperature into the experimental signal δM OBF . We assume a quasiinstantaneous correlation between the lattice distortion and the temperature-induced changes of the antiferromagnetic order parameter [39] and exploit the known temperature-dependence of the MOBF, which is given as…”
mentioning
confidence: 99%
“…This was observed directly in silicon by Harb et al (2008). Spin-lattice coupling has also recently been interrogated from the lattice perspective using UED (Tauchert et al, 2022;Windsor et al, 2021).…”
Section: Examples From Literaturementioning
confidence: 91%
“…3 the optical absorption is of at least similar strength, we can extrapolate the measured lattice temperature in ref. 3 to ~85 K given our pump fluence. We note that in ref.…”
Section: Temporal Evolution Of Afm Order Visualized At the Nickel L2-...mentioning
confidence: 99%